The Value of Neutrophil-To-Lymphocyte Ratio for Evaluating Blood Stream Infection Caused by Carbapenem-Resistant Klebsiella pneumoniae: A Retrospective Cohort Study - Wu, Heng; Mao, Yihan; Du, Xiaoxing; Zhao, Feng; Jiang, Yan; Yu, Yunsong (Frontiers in Medicine, 2022)
The neutrophil-to-lymphocyte ratio (NLR) is a useful marker of inflammation. However, the prognostic function of the NLR in patients with carbapenem-resistant Klebsiella pneumoniae (CRKP) blood stream infection (BSI) remains largely unknown. The aim of this study was to explore the potential relationship between the NLR and mortality. We performed a retrospective cohort study based on data retrieved from the computerised patient record system in a tertiary hospital from 1 January 2017 to 31 October, 2020. A total of 134 inpatients with CRKP BSI were enrolled in this study, including 54 fatal cases and 80 survival cases, 28 days after the onset of CRKP BSI. A logistic analysis was performed to assess the association between the NLR on the 4th day and 28-day mortality. Multivariate analyses were used to control for the confounders. The overall 28-day mortality rate of patients with a CRKP BSI episode was 40.3% (54/134). We conducted a multivariate analysis of the data of 134 patients and found that the NLR on the 4th day (odds ratio [OR] 1.148, 95% CI 1.076–1.225, p<0.001) and antibiotic exposure before BSI onset (OR 3.847, 95% CI 1.322–11.196, p=0.013) were independent risk factors for 28-day mortality of patients with CRKP BSI, while appropriate initial therapy (AIT, OR 0.073, 95% CI 0.017–0.307, p < 0.001) was an independent protective factor. Among patients treated with AITs, the Cox proportional hazards regression analysis revealed a significant difference in prognosis (p=0.006) between the CAZ group and non CAZ-AVI groups. Dividing the non CAZ-AVI group into the tigecycline, colistin, and TGC+COL groups, there were no differences between the CAZ-AVI and the TGC groups, but CAZ-AVI group showed lower 28-day mortality than COL (p=0.002) and TGC+COL (p=0.002) groups. Meanwhile, there was no difference in NLR on the 1st day but significant difference in NLR on the 4th day (p=0.047).The NLR on the 4th day is a readily available and independent prognostic biomarker for patients with CRKP BSI. This marker may have the potential for use in evaluating the efficacy of different anti-infection therapy strategies at an early stage.